2013
DOI: 10.2139/ssrn.2314882
|View full text |Cite
|
Sign up to set email alerts
|

What Drives the Market Share Changes? Price versus Non-Price Factors

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 31 publications
(21 reference statements)
2
25
0
Order By: Relevance
“…the standard approach to modeling exports and imports is unable to fully capture their developments. This has been confirmed by many previous studies, pointing to the importance of non-price competitiveness in international trade (ECB (2005), Dieppe et al (2011), di Mauro andForster (2008), Benkovskis and Wörz (2014), Antras et al (2010), Altomonte et al (2013)). In addition Anderton and Tewolde (2011) found that a large part of imports developments during the upturn of global trade after the crisis might be ascribed to fiscal and monetary policy measures; these were implemented to boost trade and are not captured by standard demand variables.…”
Section: Introductionsupporting
confidence: 78%
“…the standard approach to modeling exports and imports is unable to fully capture their developments. This has been confirmed by many previous studies, pointing to the importance of non-price competitiveness in international trade (ECB (2005), Dieppe et al (2011), di Mauro andForster (2008), Benkovskis and Wörz (2014), Antras et al (2010), Altomonte et al (2013)). In addition Anderton and Tewolde (2011) found that a large part of imports developments during the upturn of global trade after the crisis might be ascribed to fiscal and monetary policy measures; these were implemented to boost trade and are not captured by standard demand variables.…”
Section: Introductionsupporting
confidence: 78%
“…This enormous gain in world market shares is often ascribed to the fact that China still has relatively lower production costs, thus alluding to its price competitiveness. More recently, there is also evidence for improving quality of Chinese exporters (Pula and Santabarbara, 2011;Fu et al, 2012;Benkovskis and Wörz, 2014b). Another development that is often overlooked in such analyses is the fact that China has integrated deeper into global production networks (global value chains -GVCs) over the same period, thus the label "Made in China" also covers inputs produced by other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The starting point is the decomposition of changes in gross export market shares recently developed by Benkovskis and Wörz (2014b). According to the empirical analysis of Benkovskis and Wörz (2014b), price factors fail to explain changes in gross market share dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors that affect competitiveness, among them changes in productivity, skills and technological knowledge, the nature of public policies, the capacity to raise exports, price/cost and non-price/cost factors, etc. (de la Guardia, Molero, Valadez, 2005;Athanasoglou, Bardaka, 2010;Benkovskis, Wörz, 2017). For purposes of the research, we used a set of measures that describe four areas of competitiveness (Table 1).…”
Section: Analysis Of Basic Measures Of Competitiveness Regarding Expomentioning
confidence: 99%